P11.06.A benefits of carbohydrate loading drinks pre-operatively for patients with a presumed high-grade glioma planned for an awake craniotomy. (5th September 2022) - La, J; Bhangoo, R; Hurwitz, V; Ashkan, K; Vergani, F; Gullan, R; Lavrador, J P; Robinson, C; Kostick, E; Suarez, A; Hedges, S; Brazil, L; et al.
Abstract: Background: As part of enhanced recovery after surgery in neuro oncology, carbohydrate loading drinks were reviewed to see if there were any benefits in administering this pre operatively, in particularly for patients for awake craniotomy electively. This method is currently used in colorectal and spinal teams within the trust. Carbohydrate loading drinks are clear, and can be consumed up to 2 hours before induction of anaesthesia. Currently reviewed for patients for awake craniotomy with the vision to implement for all patients planned for craniotomy, both asleep and awake. The concept of this drink, is that it helps with post-operative nausea and vomiting, insulin resistance, helps with energy boost which is helpful during awake craniotomies and potentially during their engagement with therapists post operatively and wound healing (Hausel J et al, 2005). This could essentially lead to safer discharge, reduced risk of wound infection and reduced length of stay. Material and Methods: In a single centre, data for patients who have undergone awake craniotomies this year were abstracted. Patients planned for an awake surgery were prescribed carb-loading drinks. Due to the start date of this study, there were already a number of patients who have had their awake craniotomies without having carb-loading drinks prescribed. The data for both cohorts enabled comparison on engagement during and after awake craniotomies with therapists and length of stay. Results: The current data collected has found that the average length of stay in the group who were not prescribed carbohydrate loading drinks pre operatively, had an average length of stay 7.2 days in total, 50% had experienced nausea and vomiting post operatively, which led therapists unable to perform assessments. 66% of patients in this group were found to have some form of difficulties engaging with the therapists during the awake phase of their craniotomies. Compared with patients who were prescribed the carbohydrate loading drink, the average length of stay was 4.6 days, with no post operative nausea and vomiting, no difficulties engaging with therapists post operatively. Conclusion: Though the current data is of a small volume, carbohydrate loading pre-operatively can help patients for elective awake craniotomies and reduce length of stay in hospital, optimising their recovery in a fast yet safe manner to ensure they are in the best performance status prior to commencing oncology treatment. With further analysis into the use of carb-loading drinks pre-operatively, this can be used widely within neuro-oncology surgeries. Hausel J, Nygren J, Thorell A et al Randomized clinical trial of the effects of oral preoperative carbohydrates on postoperative nausea and vomiting after laparoscopic cholecystectomy. Br J Surg 2005; : 415-421. [PubMed] [Google Scholar]